2016
DOI: 10.3389/fimmu.2016.00581
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Is Not Constitutively Expressed on Tasmanian Devil Facial Tumor Cells but Is Strongly Upregulated in Response to IFN-γ and Can Be Expressed in the Tumor Microenvironment

Abstract: The devil facial tumor disease (DFTD) is caused by clonal transmissible cancers that have led to a catastrophic decline in the wild Tasmanian devil (Sarcophilus harrisii) population. The first transmissible tumor, now termed devil facial tumor 1 (DFT1), was first discovered in 1996 and has been continually transmitted to new hosts for at least 20 years. In 2015, a second transmissible cancer [devil facial tumor 2 (DFT2)] was discovered in wild devils, and the DFT2 is genetically distinct and independent from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 66 publications
5
64
0
Order By: Relevance
“…In line with this hypothesis, a recent study reported that overexpressing several checkpoint molecules, including CD200, PDL1, and CD47, in mouse embryonic stem cells could be used to generate teratomas that could establish long-term allograft tolerance in fully immunocompetent hosts 60 . We have previously reported that PDL1 mRNA and protein are upregulated on DFT2 cells in response to IFNγ 25 , and our transcriptome results show that CD47 is expressed at moderate to high levels in DFT cells. Here we show that overexpression of CD200R1 on DFT1 eliminates binding of our polyclonal anti-CD200 antibodies, suggesting that DFT cells overexpressing CD200R1 could be used to test the role of CD200 in allograft tolerance.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In line with this hypothesis, a recent study reported that overexpressing several checkpoint molecules, including CD200, PDL1, and CD47, in mouse embryonic stem cells could be used to generate teratomas that could establish long-term allograft tolerance in fully immunocompetent hosts 60 . We have previously reported that PDL1 mRNA and protein are upregulated on DFT2 cells in response to IFNγ 25 , and our transcriptome results show that CD47 is expressed at moderate to high levels in DFT cells. Here we show that overexpression of CD200R1 on DFT1 eliminates binding of our polyclonal anti-CD200 antibodies, suggesting that DFT cells overexpressing CD200R1 could be used to test the role of CD200 in allograft tolerance.…”
Section: Discussionsupporting
confidence: 62%
“…These have proven broadly effective in part because they function across many different MHC types and tumor mutational patterns. However, these pathways have received little attention in transmissible cancers and other naturally occurring cancers in non-model species (Figure 1, Table S1 ) 2527 . We have previously shown that the inhibitory immune checkpoint molecule programmed death ligand 1 (PDL1) is expressed in the DFT microenvironment and is upregulated by interferon-gamma (IFNγ) in vitro 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have not included the analysis of PD-1, PD-L1, and PD-L2 here, as we have previously published this information (52). Understanding the broad role of checkpoint molecules in these complex diseases has the potential to shed light on fundamental aspects of immune evasion, transplant tolerance and rejection, and infectious disease; this is logically relevant to both human and veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that cancer can weaken the immune system, however, cancer rarely acts as an infectious disease [28]. DFTD is extremely unusual that the allograft tumors are not rejected by the host immune system [29].…”
Section: Possible Mechanisms On Devil Extinctionmentioning
confidence: 99%